Varactor-Based Continuously Tunable Microstrip Bandpass Filters: A Review, Issues and Future Trends - Mengjie Qin; Zhongmao Li; Zhipeng Ren; Pengzhan Liu; Lanlan Liao; Xin Qiu; Zhiqiang Li (IEEE Access)
Electronically tuned bandpass filters are crucial frequency-selective devices in tunable RF front-ends and are extensively utilized in the fields of communications and sensing. For low-cost and easy integration, varactor based tunable microstrip filters have been widely used in circuit design. The miniaturization, tuning flexibility, and performance optimization of tunable microstrip filters are all areas of concern. This paper reviews the research conducted on the varactor-diode-based tunable bandpass filters over the past decade. Numerous filters with various structures are introduced in the following sequence: frequency tuning, frequency and bandwidth tuning, transmission zero tuning, and tunable bandpass filter with special functions. The existing problems and limitations of various types of tuned filters have been discussed. The performance of several outstanding works has been analyzed and compared. Finally, the development direction of varactor-based microstrip tunable filters is objectively summarized, which will advance the research of microstrip filters.